Models of education for care workers in Australian nursing homes: improving the care of older people - Rayner, Jo-Anne; Mahoney, Anne-Marie; Fetherstonhaugh, Deirdre; Cowen, Sandra (Frontiers in Public Health, 2025)
IntroductionProviding high-quality care in nursing homes requires a skilled and knowledgeable workforce. The Australian nursing home workforce is made up predominantly of personal care workers who are unprepared educationally to provide care to older people with complex care needs. We describe the design, development, and implementation of two education packages for Australian personal care workers to improve their knowledge and confidence in providing optimal care to older people.Methods—pedagogy and education developmentThe first package was developed following original research, which explored the need for education focusing on recognising and reporting resident deterioration, the preferred way of delivering this education, and barriers to education. Time and costs were identified as barriers, indicating that short, modular education for care workers was required. Using a train-the-trainer model, this education (10 h of delivery) comprises eight modules designed to be delivered individually or over two days by a registered nurse. The second education package was commissioned work following the interim findings from the Australian Royal Commission into Aged Care Quality and Safety and focused on three identified areas of need: dementia care, a palliative approach to care, and oral and dental care. Also modular, the second package has a learner-centric approach for the multidisciplinary aged care team and is freely available online.ResultsUser acceptability testing found the first package to be of high quality, easy to deliver, and the content can be adapted to meet individuals’ different learning styles, knowledge needs, and time availability. User acceptability testing of the second education package was undertaken in the development phase. This package has an international reach and continues to provide a popular single, easily accessible site for personal care worker education, who comprise 60% of users.ConclusionWhile research suggests that personal care workers prefer face-to-face interactive education and training, the COVID-19 pandemic has changed the education landscape, and care workers are also embracing online learning. These education packages meet the needs of the personal care workforce, providing choice and flexibility: interactive learning in the context of care delivery or freely available online learning that can be undertaken in personal time.